Education and development in Afghanistan : challenges and prospects - Bittlingmayer, Uwe H.; Grundmeier, Anne-Marie; Kössler, Reinhart; Sahrai, Diana; Sahrai, Fereschta (Global studies (Bielefeld, Germany), 2019)
After 15 years of military interventions since 2003, the current situation in Afghanistan is highly ambivalent and partially contradictory - especially regarding the interplay of development, peace, security, education, and economics. Despite numerous development initiatives, Afghanistan is still confronted with a poor security and economic condition. At the same time, enrollment numbers in schools and universities as well as the rate of academics reached a historical peak. This volume investigates the tension between these ambivalent developments. Sociologists, political and cultural scientists along with development workers, educators, and artists from Germany and Afghanistan discuss the idea that education is primary for rebuilding a stable Afghan state and government.